The ChatGPT Application: Initial Perceptions of University Teachers (LACCEI, 2024)
This research had the purpose of probing from a first teaching perception what would mean the abrupt irruption of the application of Artificial Intelligence (AI) ChatGPT regarding the academic uses that higher education students can already give to it. Of exploratory scope and basic type, the study is proposed under the interpretationist paradigm, qualitative approach and phenomenological typology it used the interview technique applying a questionnaire of open-ended questions to 23 research professors of seven university careers in Peru. The instrument covered four aspects: advantages, disadvantages, challenges and needs of ChatGPT. Among the advantages are the availability of better academic technological tools and the ability to consolidate delegated work in less time and with more sources the disadvantages are that it opens the door to higher levels of plagiarism with a high possibility of non-detection the perceived challenges focus on the demands of generating better relationships of trust and delegation from teachers to students and on developing new methods of verifying knowledge the needs point to the rapid incorporation of technological training and ethical awareness. It is concluded that an unprecedented chapter has been opened in academic opportunities and demands that would entail new dynamics between teachers and students, at academic and ethical levels, posing a scenario of demands for new technologies that support the ChatGPT application but also contain its eventual overflowing boom.